**Weegy:** 3y - 4 =6y - 19
3y -6y = -19 +4
-3y=-15
y=-15/-3
y=5

**User:** Solve for y.
12.4 + 4y = 2y + 6.4

**Weegy:** y=-2

(More)3

24.3 = 3(2 + y)

24.3 = 6 + 3y

-3y = 6 - 24.3

-3y = -18.3

y = -18.3/-3

y = 6.1

Added 9/27/2015 1:27:45 PM

This answer has been confirmed as correct and helpful.

3

8 - 3y + 6y = 9.5

8 - 3y = 9.5

-3y = 9.5 - 8

-3y = 1.5

y = 1.5/-3

y = -0.5

Added 9/27/2015 1:29:39 PM

This answer has been confirmed as correct and helpful.

3

12.4 + 4y = 2y + 6.4

4y - 2y = 6.4 - 12.4

2y = -6

y = -6/2

y = -3

Added 9/27/2015 1:30:45 PM

This answer has been confirmed as correct and helpful.